Interpreting Effectiveness Evidence in Pain: Short Tour of Contemporary Issues. Issue 8 (1st August 2015) - O'Connell, Neil E.; Moseley, G. Lorimer; McAuley, James H.; Wand, Benedict M.; Herbert, Robert D.
Abstract : There is no shortage of treatment approaches offered to people with pain. The maze of options presents patients and clinicians with difficult choices. Key to making those choices is evidence of treatment effectiveness provided by clinical trials and systematic reviews. Recent growth in the number of clinical trials and systematic reviews, of both high and low quality, makes it vital that users of this evidence—clinicians, researchers, patients, and policy makers—have the skills and knowledge to critically interpret these studies. In this review, we discuss some contemporary issues regarding evidence of effectiveness derived from clinical trials and systematic reviews—issues that we think are critical to understanding the field. We focus on evidence of treatment effectiveness in pain, although many of these issues are relevant to and transferable across the spectrum of evidence-based practice.